dinamika biomarkerjev med olimpijskim dvigovanjem uteži; raziskava spolnih razlik - Perasovic, I.; Ivišic, A. K.; Vrdoljak, D.; Foretic, N.; Pavlinovic, V.; Peric, M.; Nikolovski, Z. (Kinesiologia Slovenica, 2025)
Sports competitions are defined as highly stressful environments, especially for the athletes. Apart from psychological, stressors perceived are connected with physical exertion and physiological response. Therefore, this study aimed to investigate physiological response following dynamics of Cortisol (C), alpha-amylase (AA) and testosterone (T) biomarkers during official olympic weightlifting (OW) competition. Additionally, the goal was to evaluate the difference between OW disciplines and the competition stress impact on athletes\' nervous and endocrine systems. Lastly, the study aimed to determine the differences according to gender. The sample of participants in this study was 44 weightlifters (17 females). Their mean chronological age was 26.91 ± 7.57 years, body mass of 83.70 ± 23.01 kg, body height of 174.55 ± 11.92 cm, and training experience of 6.62 ± 6.95 years. In this study, saliva samples were collected during an official weightlifting competition and the AA activity and C and T concentrations were determined. The results showed that males have higher levels of T in pre-competition (males, 169.23 ± 52.37; females, 82.93 ± 23.46), post-snatch (males, 193.78 ± 56.77; females, 105.79 ± 36.18) and postclean and jerk measurement (males, 177.63 ± 54.63; females, 107.00 ± 36.26). However, the percentage of changes shows that females have a higher increase of T through the competition (pre-competition to post-snatch, 27.56%; pre-competition to post-clean and jerk 29.02%) compared to males (pre-competition to post-snatch, 14.51%; pre-competition to post-clean and jerk 4.96%). Conclusively, Olympic weightlifting elicits both endocrine and nervous system activity through measured biomarkers. Furthermore, the snatch is observed as more stressful than clean and jerk, for both genders. Also, females have a greater percentage of increase in T values with lower absolute levels. Hence, knowing the impact of OW on athletes\' stress different stress coping techniques should be applied in this sport.